Whither Singapore's unemployment rate? - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 2015)
In the period 1990-1999, Singapore's average annual real GDP growth was 7.3% with a coefficient of variation, which is a measure of dispersion of growth around its mean, of 0.49. The average annual total unemployment rate during this period was 1.9%. In comparison, in the period 2000-2012, when the average annual real GDP growth was 5.6% with a coefficient of variation of 0.79, the average annual total unemployment rate was 2.8%. Looking into Singapore's next 50 years, if real GDP grows at 3% on average, what does it imply for the rate of unemployment? Will slower growth coincide with more variable growth? This essay explores these questions.